2017
DOI: 10.1177/1069397117732749
|View full text |Cite
|
Sign up to set email alerts
|

Beauty Is in the Eye of Beholder: Intracultural and Transcultural Heterogeneity of Individuals

Abstract: Most cross-cultural studies unintentionally give the impression that there is intracultural homogeneity. This research is among a few that suggests otherwise, that there is intracultural and transcultural individual heterogeneity in thinking and logic, or "Mindscape." It is a replication and an expansion of the earlier study. It intends to verify the existence of intracultural heterogeneity in support of mindscape theory. In doing so, it employs a unique way of data collection and analysis. The analysis of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Venaik and Midgley, 2015) and empirically tested (e.g. Fatehi and Priestley, 2018; Fatehi et al, 2015, 2018). This position not only is a realistic one, and intuitively appealing, but research by many scholars suggested intracultural heterogeneity ( e.g.…”
Section: Mindscape Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Venaik and Midgley, 2015) and empirically tested (e.g. Fatehi and Priestley, 2018; Fatehi et al, 2015, 2018). This position not only is a realistic one, and intuitively appealing, but research by many scholars suggested intracultural heterogeneity ( e.g.…”
Section: Mindscape Theorymentioning
confidence: 99%
“…Au, 1999, 2000; Au and Cheung, 2004; Brewer and Venaik, 2012; Gurven et al, 2008; Kirkman et al, 2006; McSweeney, 2002a, 2002b, 2013; Tung, 2008), and both, inter- and intracultural heterogeneity (e.g. Fatehi and Priestley, 2018, Fatehi et al 2015, 2018; and Maruyama’s extensive writings on the Mindscape Theory, 1980–2004). In all cultures, some individuals have similarities in logic, values, beliefs, and behavior with some people of their own and or other cultures.…”
Section: Mindscape Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have applied TOB tests in many countries Fatehi et al (2015), Fatehi and Priestley (2018), Maruyama et al (1998, 2002), Yolles and Fink (2009, 2016) and confirmed the Mindscape theory. However, neither Maruyama’s research nor any of the many studies that followed attempted to identify the correspondence between the four major Mindscape types and the specific TOB tests’ geometric patterns.…”
Section: Introductionmentioning
confidence: 87%
“…“We can improve the present state of knowledge accumulation through encouraging more replication” (Tsang and Kwan, 1999, p. 771). “A replication may not provide any new information; it could be just a confirmation or refutation of the original study” (Fatehi and Priestley, 2018, p. 446). While this study replicates a previous one, it has a couple of differences from the original.…”
Section: Introductionmentioning
confidence: 99%